Facilitation and biodiversity–ecosystem function relationships in crop production systems and their role in sustainable farming. (15th February 2021) - Brooker, Rob W.; George, Tim S.; Homulle, Zohralyn; Karley, Alison J.; Newton, Adrian C.; Pakeman, Robin J.; Schöb, Christian
Abstract: We review the need for increasing agricultural sustainability, how this can in part be delivered by positive biodiversity–ecosystem function (BEF) effects, the role within these of plant–plant facilitation, and how a better understanding of this role may help to deliver sustainable crop (particularly arable) production systems. Major challenges facing intensive arable production include overall declines in biodiversity, poor soil structure and health, nutrient and soil particle run‐off, high greenhouse gas emissions, and increasing costs of synthetic inputs including herbicides, pesticides and fertilisers. Biodiversity–ecosystem function effects have the potential to deliver win–wins for arable food production, whereby enhanced biodiversity is associated with 'good outcomes' for farming sustainability, albeit sometimes through negative BEF effects for some components of the system. Although it can be difficult to separate explicitly from niche differentiation, evidence indicates facilitation can be a key component of these BEF effects. Explicit recognition of facilitation's role brings benefits to developing sustainable crop systems. First, it allows us to link fundamental ecological studies on the evolution of facilitation to the selection of traits that can enhance functioning in crop mixtures. Second, it provides us with analytical frameworks which can be used to bring structure and testable hypotheses to data derived from multiple (often independent) crop trials. Before concrete guidance can be provided to the agricultural sector as to how facilitation might be enhanced in crop systems, challenges exist with respect to quantifying facilitation, understanding the traits that maximise facilitation and integrating these traits into breeding programmes, components of an approach we suggest could be termed 'Functional Ecological Selection'. Synthesis . Ultimately, better integration between ecologists and crop scientists will be essential in harnessing the benefits of ecological knowledge for developing more sustainable agriculture. We need to focus on understanding the mechanistic basis of strong facilitative interactions in crop systems and using this information to select and breed for improved combinations of genotypes and species as part of the Functional Ecological Selection approach. Abstract : We review the need for increasing agricultural sustainability, how this can be partly delivered by positive biodiversity–ecosystem function (BEF) effects, the role within these of plant facilitation, and how better understanding of this role may help to deliver sustainable crop production systems. We also explore how ecological approaches such as the Stress Gradient Hypothesis can help deliver this goal.